"Thick Section" Gram Stain Yields Improved Detection of Organisms in Tissue Sections of Cystic Neutrophilic Granulomatous Mastitis. Issue 5 (12th December 2019) - Sangoi, Ankur R
Abstract: Objectives: Cystic neutrophilic granulomatous mastitis (CNGM) is an uncommon subtype of granulomatous mastitis featuring epithelioid histiocytes/neutrophils rimming discrete cystic spaces. When present, gram-positive bacteria (typically Corynebacterium species) are identified within these cystic spaces, although they can be difficult to appreciate on tissue sections. Methods: Based on pilot gram-stained tissue sections of CNGM cases cut on 6 μm thickness (in which bacterial organisms were more readily identifiable) instead of the traditional 4 μm, a formal comparative analysis of 19 CNGM cases was performed on parallel 6-μm ("thick") vs 4-μm sections from one representative block per case. Results: Biopsies (n = 17) and excisional specimens (n = 2) from 19 CNGM cases were included. Gram-positive palisaded rods were identified in seven cases using 4-μm sections and in 11 cases using 6-μm sections (sensitivity of 37% vs 58% in identifying organisms). Among all seven cases of organisms seen on the 4-μm section Gram stain, the paired 6-μm section Gram stain showed a higher number of and more readily identifiable bacteria. Conclusions: Thick section Gram stain of representative tissue blocks performed at 6 μm improves both detection rate and ease of identification of gram-positive organisms in CNGM.